Public Health Promotion and Education with Hypertension Awareness in West Jakarta Indonesia - Erlina Puspitaloka Mahadewi; Intan Silviana Mustikawati; Ade Heryana; Arman Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
The present study reports are the comprehensive study on the awareness of hypertension which is a dangerous disease with an increase in blood pressure above normal values. According to the study, hypertension is an increase in systolic blood pressure of about 140 mmHg or diastolic pressure of about 90 mmHg. Hypertension is a problem that needs to be watched out for, because there are no specific signs of hypertension and some people still feel healthy to carry out their usual activities. This is what makes hypertension a silent killer by data of Indonesia Ministry of Health, 2018, people will realize they have hypertension when the symptoms they feel are getting worse and go to health services. The purpose of this health promotion is to provide information and education to the public about hypertension and its prevention in Tegal Alur Village, Kali Deres District, West Jakarta. Health promotion activities are carried out online using the online via zoom meet application with lecture, question and answer and discussion methods. To determine the effectiveness of health promotion activities, such healthy living community movement or known as Germas, to the community members were given a questionnaire before (pre-test) and after the activity (post-test). Based on the post-test results, it was found that there was an increase in knowledge about hypertension. Plans and achievement targets for the follow-up to the implementation of this activity can be carried out in collaboration with all parties, namely the government, campuses and the wider surrounding community to create a community movement in creating behavior and awareness of hypertension prevention itself.